Glacial history of the upper Drac Blanc catchment (French Alps) - Hofmann, Felix Martin (2018)
Glacier advances in the Écrins massif (French Alps) during the Late Glacial and the Early Holocene are poorly constrained. Based on field observations, a high-resolution digital elevation model and an orthophoto, glacial landforms in the upper Drac Blanc catchment were mapped. Thanks to 42 new 10Be exposure ages, the timing of the stabilisation of selected moraines was constrained. The application of the accumulation area ratio method with a ratio of 0.67 enabled the determination of the Equilibrium Line Altitude (ELA) during the corresponding glacier advances and the amount it lowered compared to the end of the Little Ice Age. The lowermost sampled moraine may have been reached by a first glacier advance at around 16.9 ± 1.6 ka. Not unexpectedly, multiple moraines in the upper Drac Blanc catchment stabilised during Greenland stadial 1 and in the Early Holocene. During the furthest glacier advance somewhat before 12.5 ± 0.6 ka, a prominent moraine was shaped or, alternatively, re-occupied. The 10Be exposure ages provide evidence for further glacier advances or halts in glacier recession not later than 12.5 ± 0.6, 11.9 ± 1.0 and 11.2 ± 0.4 ka. According to the ELA reconstructions, these events were associated with ELA depressions between 160 and 220 m with respect to the end of the Little Ice Age. Exposure ages from three boulders indicate a still stand or a glacial readvance not later than 10.7 ± 0.6 ka when the ELA was 150 m lower than at the end of the Little Ice Age. Novel findings of this study are (1) the periods of moraine stabilisation at the latest at 11.9 ± 1.0, 11.2 ± 0.4 and 10.7 ± 0.6 ka which have hitherto not been dated in the Écrins massif and (2) the associated ELA lowering during these periods based on the accumulation area ratio method. The 10Be exposure ages agree well with that of moraines at other sites in the Alps which have been correlated with the Egesen and the Kartell stadials.